PISICHIK DEVELOPMENT OF BEHAVIOR IN PRESCHOOL CHILDREN (American Journal of Research in Humanities and Social Sciences, 2023)
Preschool years are a very important period for the development of behavior in children. During this period, children begin to establish the world around them, form relationships, learn social norms, develop emotional and self-regulatory skills. In this article, we will study various aspects of the development of behavior in preschool children.